A comparative study of volatile components of propolis (bee glue) collected from Haramaya University and Assela Beekeeping Centers, Ethiopia - Kesatebrhan Haile; Tesfahun Kebede; Aman Dekebo (Bulletin of the Chemical Society of Ethiopia, 2012)
The investigation of the volatile compounds of essential oils of propolis from two geographic origins of Ethiopia (Haramaya and Assela) was made by GC-MS. A total of 62 components of the oil were identified from both samples. The identified constituents of the oils may be divided into seven different groups: oxygenated monoterpenes (29.81% Haramaya, 9.45% Asella), sesquiterpenes (15.20% Haramaya, 19.05% Assela), oxygenated sesquiterpenes (11.86% Haramaya, 18.56% Assela), aromatic (14.93% Haramaya, 4.25% Assela), oxygenated aromatic (17.59% Haramaya, 4.58% Assela), aliphatic (5.06% Haramaya, 7.62% Assela) and oxygenated aliphatic (7.84% Haramaya, 25.17% Asella). The major volatile compounds of Haramaya propolis consist of calamenene (13.82%), 4-terpineol (8.57%), epi-bicyclosesquiphellandrene (8.37%), 4-(2-acetyl-5,5-dimethylcyclopent-2-enylidene)butan-2-one (7.83%) and 3-isopropyl-6-methyl-2-oxo-1-(3-oxobutyl)-cyclo- hexanecarbaldehyde (5.90%). Whereas the most abundant constituents of Assela propolis were 5,6,7,8-tetramethylbicyclo[4,1,0]hept-4-en-3-one (15.01%), acoradien (13.77%), epicedrol (6.80%) and (6E,6E)-3,7,11,15-tetramethyl-1,6,10,14-hexadecatetraen-3-ol (6.14%). Ten compounds which were found in both samples of propolis were trans-pinocarveol, α-cadinol, cis-verbenol, α-campholenal, 4-terpineol, p-cymen-8-ol, p-menth-1-en-8-ol, epi-bicyclosesquiphellandrene, calamenene and 3-isopropyl-6-methyl-2-oxo-1-(3-oxobutyl)-cyclohexanecarbaldehyde.DOI: http://dx.doi.org/10.4314/bcse.v26i3.4